Coach development programmes to improve interpersonal coach behaviours: a systematic review using the re-aim framework - Evans, M. B.; McGuckin, M.; Gainforth, H. L.; Bruner, M. W.; Côté, J. (British Journal of Sports Medicine, 2015)
Objective: Although evidence supports the effectiveness of interpersonal Coach Development Programmes (CDPs), which are designed to foster coach-athlete relationships, an intervention's impact is shaped by numerous factors over and above effectiveness. The purpose of this systematic review was to examine the extent that published articles describing interpersonal CDP trials reported on indicators of internal and external validity, as conceptualised in the RE-AIM framework (ie, Reach, Effectiveness, Adoption, Implementation and Maintenance). Methods: The search strategy was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines, involving a database search and supplemental manual search of key articles and journals. After initial screening, the full-text search strategy involved identifying articles describing CDP trials and then selecting a specific subgroup of articles involving interpersonal CDP trials and excluding ineligible articles. Resulting trials were coded using a 47-item sport coaching adaptation of the RE-AIM coding sheet. Results: 17 published articles met eligibility criteria, representing 10 distinct CDP trials. After attaining coder agreement, global ratings of RE-AIM indicators within interpersonal CDP trials ranged from the low to moderate quality. Whereas indicators of effectiveness and implementation were reported to some extent across all studies, maintenance within sport organisations and a number of specific indicators from across dimensions were rarely reported. Conclusions: These findings inform the future design and evaluation of CDPs that have the potential to be adopted in numerous settings and reach athletes and coaches who can most benefit.